Strategi Pedagang Dalam Meningkatkan Ekonomi Keluarga Di Pantai Sire Kabupaten Lombok Utara - Syarifa Nurus Sifak; Melati Sukma Dewi; Ani Mahyuni; Muhamad Iqrom; Ika Wijayanti (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Sire Beach is one of the favourite tourist destinations in the North Lombok district. However, the name Sire beach is still not as popular as the other tourists like the three Gili that are in Lombok North district (Gili Terawangan, Gili Meno, dan Air). The researchers used qualitative methods to study issues on the Sire Coast. Data collection using observation techniques, in-depth interviews, and documentation. The determination of the informant is done using proporsive techniques consisting of the Chief of the Board, the Trader, and the tourist. The data analysis technique is done by collecting data, reducing the data, presenting data and drawing conclusions. Research results show that although the Sire coast has a high tourism potential, traders still face several challenges including the lack of support from local governments and the poor innovation of traders in boosting the family economy.